Clinical manifestations of primary and secondary dengue in Paraguay and its relation to virus serotype - Dolores Lovera; Celia Martínez-Cuellar; Fernando Galeano; Sara Amarilla; Cynthia Vazquez; Antonio Arbo (Journal of Infection in Developing Countries)
Introduction: Dengue virus (DENV) infection is currently a major cause of morbidity in the world, and its incidence has mainly increased during the last years in Latin America, including Paraguay. The objective of this study was to compare the clinical and laboratory findings of dengue and assess whether the serotype is a risk factor for severity.